Gellan gum: a new biomaterial for cartilage tissue engineering applications - Oliveira, J. T. (2010)
Gellan gum is a polysaccharide manufactured by microbial fermentation of the Sphingomonas paucimobilis microorganism, being commonly used in the food and pharmaceutical industry. It can be dissolved in water, and when heated and mixed with mono or divalent cations, forms a gel upon lowering the temperature under mild conditions. In this work, gellan gum hydrogels were analyzed as cells supports in the context of cartilage regeneration. Gellan gum hydrogel discs were characterized in terms of mechanical and structural properties. Transmission electron microscopy revealed a quite homogeneous chain arrangement within the hydrogels matrix, and dynamic mechanical analysis allowed to characterize the hydrogels discs viscoelastic properties upon compression solicitation, being the compressive storage and loss modulus of !40 kPa and 3 kPa, respectively, at a frequency of 1 Hz. Rheological measurements determined the sol-gel transition started to occur at approximatel 368C, exhibiting a gelation time of !11 s. Evaluation of the gellan gum hydrogels biological performance was performed using a standard MTS cytotoxicity test, which showed that the leachables released are not deleterious to the cells and hence were noncytotoxic. Gellan gum hydrogels were afterwards used to encapsulate human nasal chondrocytes (1 3 106 cells/mL) and culture them for total periods of 2 weeks. Cells viability was confirmed using confocal calcein AM staining. Histological observations revealed normal chondrocytes morphology and the obtained data supports the claim that this new biomaterial has the potential to serve as a cell support in the field of cartilage regeneration.